(untitled) (قضايا سياسية, 2023)
Modern and contemporary political thought dealt with several concepts, until various interpretive schools of thought emerged to solve and explain the problems in clarifying the concepts, some of which provided solutions for that and some that did not, and among the terms whose problems were not resolved is the concept of political authoritarianism; This is due to the multiplicity of opinions about it, as well as the overlap of many concepts and terminology about the content and essence of political authoritarianism. The term political authoritarianism is among the most controversial terms in the political science literature, and the lack of agreement on defining a unified meaning for it still represents a clear problem in the term’s instability. Especially since the overlap that the term witnesses with other terms clearly justifies this problem and the lack of independence of the concept. It should be noted that most social science concepts, including political science concepts, require, in the process of understanding and studying them, to dismantle the terms, search for their content in detail, and then reconstruct them in a way that ensures the presentation of an academic concept that can provide theoretical approaches that give the concept its academic due .